2007
DOI: 10.1007/s12011-007-9024-0
|View full text |Cite
|
Sign up to set email alerts
|

In Situ effect of strontium toothpaste on artificially decalcified human enamel

Abstract: The aim of this study was to measure the strontium levels in surface and subsurface artificially decalcified enamel exposed in situ to a strontium-supplemented toothpaste. Twenty healthy premolar teeth extracted for orthodontic reasons were cut into blocks and demineralized. The samples were cemented to the teeth of six volunteers who brushed with a hydroxyapatite (HAP) and HAP strontium-supplemented toothpaste for 3 and 6 mo. The strontium content in the enamel surface and in the lateral wall of the enamel sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…It has indeed been shown that brushing teeth with strontium-supplemented toothpastes increased the strontium content in the exposed enamel, as early as 3 weeks into treatment. This increase in strontium content is suggested to be advantageous in the treatment of cariogenesis [103].…”
Section: Strontiummentioning
confidence: 99%
“…It has indeed been shown that brushing teeth with strontium-supplemented toothpastes increased the strontium content in the exposed enamel, as early as 3 weeks into treatment. This increase in strontium content is suggested to be advantageous in the treatment of cariogenesis [103].…”
Section: Strontiummentioning
confidence: 99%
“…Consequently, a number of strontium-containing materials have been extensively used as a bone filler, such as partially strontium-substituted HAp [2][3][4][5], a-tricalcium phosphate [6] and CaSiO 3 [7], as well as strontium-containing cement [8,9]. In addition, strontium-containing toothpaste was developed to enhance the remineralization of dental enamel [10], and recently drugs such as strontium ranelate (SrR) [11] have been suggested for use as a daily supplement to increase bone mineral density.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the present study did not have any criteria about the use of toothpastes that may affect levels of Sr and Sn. Although Sr compounds are toxic to humans in high doses , they were not reported to be at toxic levels in toothpastes. Sn is reported as an element with low toxicity .…”
Section: Discussionmentioning
confidence: 99%